Prevalence, trends, and inequality in noncommunicable diseases in Bangladesh: Evidence from Bangladesh Demographic and Health Surveys 2011 and 2017–2018 - Ali, Masum; Amin, Md. Ruhul; Jarl, Johan; Saha, Sanjib (Wiley, 2024)
We investigated the change of the prevalence of noncommunicable diseases (NCDs) in Bangladesh from 2011 to 2018 across different socioeconomic groups as well as the factors associated with the changes in prevalence. We used the two waves of the Bangladesh Demographic and Health Surveys conducted in 2011 and 2017–2018. Modified Poisson regression model was used to estimate the prevalence rate and ratio of NCDs and to test the association with different demographic and socioeconomic variables. The study found an upward trend of NCDs from 2011 to 2017 in which overweight and obesity, hypertension, and diabetes increased by 1.8, 1.5, and 1.1 times, respectively. In 2011, people from the richest households had 5.6 higher odds of being overweight compared to the poorest, which was reduced to 3.0 in 2017. However, the increment for overweight and hypertension was the highest among the poor and manual workers from 2011 to 2017. The age-adjusted prevalence ratio of overweight increased 4.4 times for the poorest, compared to 1.7 times for the richest. For manual workers, overweight increased 3.8 times, whereas hypertension increased by 2.4 times. The pooled analysis revealed that participants from the richest households have the highest risk of NCDs, with 3.3 times for overweight, 2.3 times for diabetes, and 1.3 times for hypertension, compared to the poorest. However, the prevalence of NCDs is rising quickly among the low socioeconomic groups in Bangladesh, narrowing the gap with higher socioeconomic groups. Our findings call for immediate policy interventions and targeted programs to curb NCD escalation in Bangladesh.